Acute and medium term results of balloon expandable stent placement in the transverse arch—a multicenter pediatric interventional cardiology early career society study. Issue 6 (9th September 2020) - Shahanavaz, Shabana; Aldoss, Osamah; Carr, Kaitlin; Gordon, Brent; Seckeler, Michael D.; Hiremath, Gurumurthy; Seaman, Cameron; Zablah, Jenny; Morgan, Gareth
Abstract: Objectives and Background: Coarctation of the aorta represents 5–8% of all congenital heart disease. Although balloon expandable stents provide an established treatment option for native or recurrent coarctation, outcomes from transverse arch (TAO) stenting, including resolution of hypertension have not been well studied. This study aims to evaluate immediate and midterm results of TAO stenting in a multi‐center retrospective cohort. Methods: TAO stenting was defined as stent placement traversing any head and neck vessel, with the primary intention of treating narrowing in the transverse aorta. Procedural details, complications and medications were assessed immediately post procedure, at 6 month follow‐up and at most recent follow‐up. Results: Fifty‐seven subjects, 12 (21%) native, and 45 (79%) surgically repaired aortic arches, from seven centers were included. Median age was 14 years (4 days–42 years), median weight 54 kg (1.1–141 kg). After intervention, the median directly measured arch gradient decreased from 20 mmHg (0–57 mmHg) to 0 mmHg (0–23 mmHg) ( p  < .001). The narrowest arch diameter increased from 9 mm (1.4–16 mm) to 14 mm (2.9–25 mm) ( p  < .001), with a median increase of 4.9 mm (1.1–10.1 mm). One or more arch branches were covered by the stent in 55 patients (96%). There were no serious adverse events. Two patients warranted stent repositioning following migration during deployment. There were no late complications. There were 8 reinterventions, 7 planned, and 1 unplanned (6 catheterizations, 2 surgeries). Antihypertensive management was continued in 19 (40%) at a median follow‐up of 3.2 years (0.4–7.3 years). Conclusions: TAO stenting can be useful in selected patients for resolution of stenosis with minimal complications. This subset of patients are likely to continue on antihypertensive medications despite resolution of stenosis.